Surface site modulations by conjugated organic molecules to enhance visible light activity of ZnO nanostructures in photocatalytic water splitting - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Journal of Physical Chemistry C, 2015)
Surface modification of ZnO nanoparticles is identified as a method of modulating surface sites advantageously. ZnO nanoparticles of two different sizes are surface modified with a conjugated organic moiety to enable electron conduction and transfer. Enhanced H-2 evolution from water-methanol mixtures was observed in the composite systems compared to pristine ZnO under visible light irradiation without any cocatalyst. The system is also marginally active in water splitting in pure water without any sacrificial agents. Photophysical characterization indicates that even though reducing size into the nanoregime affects the band gap detrimentally, modifications by simple conjugated organic molecules assist in enhanced visible light activity. The experimental observations are corroborated with computational studies, which also point to a localization of valence band maximum of the interface on the organic moiety and conduction band minimum on ZnO.

Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Sensitizing with short conjugated molecules: multimodal anchoring on ZnO nanoparticles for enhanced electron transfer characteristics, stability and H-2 evolution - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Catalysis Today, 2018)
Sensitizing semiconductors with organic dyes is usually employed to improve efficiency of semiconductors towards visible light absorption and charge transport. However, till date most of the dyes are either noble metal based with complex and expensive synthesis procedure or have a very narrow absorption band. Further the photostability of the dyes is another important issue. In this work we have studied, using a combination of photophysical and computational methods, ZnO nanoparticles sensitized with transition metal free, cheap and easy to synthesize azoquinoline dye that has been designed to have multiple chelating sites, viz., carboxylic group and hydroxyl imine group as a photocatalyst for water splitting activity. We find that the presence of multiple chelating sites facilitates dual mode of anchoring on ZnO nanoparticles, which leads to enhanced photostability and H-2 generation of the composite. This is attributed to the incorporation of resonance features in the dye that increases electron transfer between ZnO and dye in contrast to the charge accumulation and photo degradation observed in non-conjugated and single site anchoring counterparts. Electron transfer from ZnO to dye under UV light and reverse in visible light could be identified experimentally. Such simple designing aspects can aid in identifying better catalysts for photocatalytic water splitting.

Descriptors to predict dye-sensitized semiconductor based photocatalyst for hydrogen evolution reaction - Sappati, Subrahmanyam; George, Leena; Swamy, Vincent Paul; Devi, R. Nandini; Ghosh, Prasenjit (ChemCatChem, 2019)
Discovering efficient photocatalysts for hydrogen production from water splitting is highly desirable. Computational studies can help in rational designing of such catalysts through high throughput screening of materials. However, for that purpose one needs to identify descriptors that not only connects material properties with their functionality but are easy and inexpensive to compute. Using a combination of density functional theory based calculations and experiments we show two descriptors, namely, charge injection efficiency and electron hole separation, that can be used for in silico design of new and efficient dye-sensitized-semiconductor composites as catalysts for hydrogen evolution reaction.
Keywords: charge injection; descriptor; dye-sensitized semiconductors; electron-hole separation; H-2 evolution

Electronic, magnetic, and mechanical properties of co-doped GaSb: A promising diluted magnetic semiconductor - Samant, Ramnath; Saraf, Deepashri; Adhikari, Rajendra P.; Shilkar, Omkar; Raikar, Sakshit; Silveira, Allan; Sawant, Manthan; Sappati, Subrahmanyam; Joshi, Niharika; Desai, Ashish M. (Journal of Magnetism and Magnetic Materials, 2025)
{Understanding the interplay between magnetism and the electronic structure is crucial for the development of novel spintronic materials. This study employs density functional theory (DFT) calculations to investigate these properties in cubic Gallium Antimonide (GaSb) doped with Cobalt (Co) (Ga1-xCoxSb
Keywords: Density functional theory; Dilute magnetic semiconductors; Electronic properties; GaSb; mechanical properties; Spintronic materials